ANALISIS KETERAMPILAN PROSES SAINS ANAK DALAM KEGIATAN MENANAM SAYURAN DI RUMAH BERSAMA ORANG TUA DI MASA NEW NORMAL - Indri Dwi Isnaini (JCE (Journal of Childhood Education), 2020)
Science for early childhood can provide positive experiences for children which help them to develop an understanding of a science process skill, develop thinking skills and can instill a positive attitude. The activity to analyze science skills in children in this study was to grow vegetables at home with the mother. The purpose of this vegetable growing activity was to analyze the science process skills of ananda KZ. The research method used in this research is descriptive qualitative research. The data collection process uses observation, interview and documentation techniques. From the results of the analysis it can be concluded that ananda KZ already has scientific skills which consist of the ability to observe, compare, classify, measure, predict, and communicate messages well.